Bio-molecule adenine building block effectively enhances electromagnetic interference shielding performance of polyimide-derived carbon foam. (August 2019) - Li, Chengfeng; Zhou, Chuxiang; Lv, Jiangbo; Liang, Bo; Li, Renke; Liu, Yao; Hu, Jianghuai; Zeng, Ke; Yang, Gang
Abstract: Heteroatom doping porous carbon material possess a variety of attractive functionality such as electrical properties, catalytic properties and adsorptive capability. As an important building block of DNA, adenine has following characteristics: 1. Heterocyclic structure 2. Potential interaction modes 3. Flexible structure tailor ability 4. Available from biomass. In this study, adenine-containing polyimide (API) foam has been prepared by freeze-drying, and is used as polymer precursor of nitrogen doping carbon foam (ACF). The carbon foam (PCF) prepared by adenine-free PI foam (PMDA ODA PI) is used as a comparison. The results show that the nitrogen content of ACF after carbonization at 1000 °C (ACF-1000) is as high as 4.35%, which is about twice higher than PCF-1000 (1.90%). The conductivity of ACF-1000 is 7.11 × 10 −1 s cm −1, which is 38.06% larger than PCF-1000 (5.15 × 10 −1 s cm −1 ). The electromagnetic interference shielding effectiveness (EMI SE) of ACF-1000 is 41.1 dB, which is 26.85% higher than PCF-1000 (32.4 dB). The SSE/d (defined as the SE divided by the thickness and density of the shielding material) of ACF-1000 is 13569 dB cm 2 /g, which is 66.41% higher than PCF-1000 (8154 dB cm 2 /g). This work shows that adenine is a promising nitrogen-doping building block for polymer-derived carbon materials. The introduction of adenine structure into the polymer is helpful for improving the EMI shielding performance of carbonized products. Graphical abstract: Adenine building block can effectively enhance electrical conductivity (7.11 × 10 −1 s cm −1 ), and electromagnetic interference shielding performance (∼41.1 dB and 13569 dB cm 2 /g at 13 mm thickness) of polymer-derived carbon foam.Image 1